Pemberian Amnesti Dan Abolisi Dalam Tindak Pidana Korupsi: Tinjauan Hukum Dan Analisis Keadilan Prosedural - Hidayah, Siti; Nugroho, Aris Setyo (Indonesian Journal of Law and Justice, 2025)
The phenomenon of granting amnesty to Hasto Kristiyanto and abolition to Tom Lembong in 2025 has raised serious public debate, especially regarding the potential politicization of these legal instruments. Writer discusses the practice of granting amnesties and abolitions in corruption crimes in Indonesia, with a focus on analyzing procedural justice and legal proportionality. The research uses a normative juridical method with statutory, conceptual, and philosophical approaches. The results of the study show that the involvement of the Dewan Perwakilan Rakyat (DPR) in the consideration of amnesty and abolition has the potential to shift the President's prerogative function into a negotiation and  political instrument. This condition can weaken the principle of justice, eliminate the deterrent effect, and damage legal consistency. Therefore, the amnesty and abolition mechanism needs to be reformulation to be in line with the principle of proportional justice and ensure legal certainty.